Sustainability Practices in Small Business Ventures: Assessing the Integration of Environmental and Social Responsibility in Entrepreneurial Ventures - Asbullah, M; Tarigan, Budi Akhmad (IJBLE Scientific Publications Community Inc., 2024)
This study investigates the integration of sustainability practices in small business ventures and its impact on business performance. A cross-sectional survey approach was employed to collect data from 300 small businesses across various industries. Descriptive statistics, reliability tests, correlation analysis, and multiple regression analysis were conducted to analyze the data. The results indicate a significant positive relationship between environmental responsibility, social responsibility practices, and business performance. External support mechanisms, including government incentives and industry associations, also showed a significant positive influence on sustainability adoption. The findings suggest that small businesses can enhance their performance by prioritizing sustainability practices and leveraging external support. This study contributes to the understanding of sustainable business practices in small ventures and offers actionable insights for small business owners and policymakers.